Answer:
(x-4)2=-13
Step-by-step explanation:
2x+13=8
2x-8=-13
2(x-4)=-13
Answer:
Step-by-step explanation:
1=34
2=21
3=27
4=16
5=51
6=21
7=17
8=72
9=80
10=13
Answer:
12
Step-by-step explanation:
Use the pythagorean theorem (
). A and b are the two legs of the triangle, and c is ALWAYS the hypotenuse. Plug in the values for a and c
![a^2+b^2=c^2](https://tex.z-dn.net/?f=a%5E2%2Bb%5E2%3Dc%5E2)
![5^2+b^2=13^2](https://tex.z-dn.net/?f=5%5E2%2Bb%5E2%3D13%5E2)
![25+b^2=169](https://tex.z-dn.net/?f=25%2Bb%5E2%3D169)
![b^2=144](https://tex.z-dn.net/?f=b%5E2%3D144)
![b=12](https://tex.z-dn.net/?f=b%3D12)
Changchun. eh just h dhchre
The answer is $53
<span>x - age in years
y - total value in dollars
</span>
If the equation is y = 2x + 15, then after 19 years, the value will be:
x = 19
y = 2x + 15
y = 2 * 19 + 15
y = 38 + 15
y = 53